Unveiling Community Empowerment Strategies: Lessons from Indonesia and Malaysia in Comparative Perspective - Rosmia, Ade Romi; Wahyudin, Uyu; Inoe, Hiromu (Journal of Innovation in Educational and Cultural Research, 2025)
Community empowerment plays a crucial role in sustainable and inclusive national development. This study compares community empowerment strategies in Indonesia and Malaysia, with a focus on the impacts of decentralized and centralized approaches. The objective is to analyze how these approaches influence community participation, poverty alleviation, and infrastructure development. Employing a qualitative literature review methodology, data were collected from key government programs, such as Indonesia's National Program for Community Empowerment (PNPM) and Village Fund (Dana Desa), as well as Malaysia's Federal Land Development Authority (FELDA) and Majlis Amanah Rakyat (MARA). Findings indicate that Indonesia's decentralized model promotes local innovation and ownership, aligning development with the specific needs of individual communities. Conversely, Malaysia's centralized model ensures efficiency and uniformity but limits local involvement. The study concludes that both approaches have strengths and weaknesses: decentralization enhances community participation, while centralization ensures coordination and efficiency. This research contributes to the literature by proposing a hybrid framework that integrates both approaches, offering a comprehensive model for advancing community empowerment initiatives in diverse socio-economic contexts, particularly in developing countries.